ANALISIS UI DAN UX APLIKASI HALODOC TERHADAP PENGGUNA LAYANAN KESEHATAN - Mario Dopades; Rully Sumarlin; Tiara Radinska Deanda (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
As an application, Halodoc provides a user interface (UI) and user experience (UX) for its users to access health services more easily. When compared to many competitors that are similar to the application, Halodoc has interesting advantages that deserve to be thoroughly investigated. The mixed method is used because the research aims to find out the relationship between UI & UX based on data sources and measured data sources. The quantitative data sources are taken from the user surveys, and then the qualitative method is conducted to describe studies related to UI & UX principles and visual elements in a design. Thus, the research shows that UI & UX have a positive relationship. The better the UI & UX of the Halodoc application, the more it affects the users’ motivation to use application-based health services. This study is useful for determining the relationship between UI and UX in meeting the needs of Halodoc application health service users, as well as how the level of UX is perceived by the users. Keywords: User Interface, User Experience, Halodoc, Application